Analysis of the Frequency of Antihypertensive Drug Use at the Outpatient and Inpatient Pharmacy - Rauf, Shalwa Azahrah; Tuloli, Teti Sutriyati; Paneo, Mohamad Aprianto; Abdulkadir, Widy Susanti; Makkulawu, Andi (Jambura Nursing Journal, 2026)
The use of antihypertensive drugs at Faisal Islamic Hospital, Makassar, wasanalyzed in this study, considering the high prevalence of hypertension in Makassar, which reached 290,247 cases in 2020. Hypertension is a serious condition that requires appropriate management; thus, evaluating patterns of drug use in healthcare facilities is highly important. Specifically, this study focused on identifying the types, calculating the quantities, and analyzing the frequency of antihypertensive drug prescriptions at both outpatient and inpatient pharmacies during the period from February to April. The study employed a quantitative approach with a descriptive observational design and a retrospective case series method. Data were obtained from drug utilization reports and subsequently analyzed. To examine differences in the frequency of drug use across months, the Friedman test was applied using the SPSS statistical software. The findings revealed that 18 types of antihypertensive drugs were available at the hospital. Among them amlodipine 10 mg was the most frequently used, accounting for 27.54% of total prescriptions. Statistical analysis using the Friedman test yielded a significance value (Asymp. Sig) of 0.008. Since this value was lower than 0.05, it indicated a statistically significant difference in the frequency of antihypertensive drug use across different months. In conclusion, although amlodipine 10 mg was the predominant choice, significant variations were observed in the pattern of antihypersensitive drug use at Faisal Islamic Hospital, Makassar, during the study period.